2009
DOI: 10.1016/j.jacc.2009.07.041
|View full text |Cite
|
Sign up to set email alerts
|

Soluble ST2 for Predicting Sudden Cardiac Death in Patients With Chronic Heart Failure and Left Ventricular Systolic Dysfunction

Abstract: Elevated sST2 concentrations are predictive of SCD in patients with chronic HF and provide complementary information to NT-proBNP levels. A combined biomarker approach may have an impact on clinical decision-making.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
127
3
16

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 221 publications
(154 citation statements)
references
References 38 publications
8
127
3
16
Order By: Relevance
“…The circulating biomarker, soluble ST2 (sST2) has been shown to be a powerful independent prognosticator for patients with acute myocardial infarction (AMI)1, 2 as well as acute decompensated3, 4 and chronic5, 6, 7, 8, 9 HF. sST2, a member of the interleukin (IL)‐1 receptor‐like family of proteins, is released in response to myocyte stretch, and functions as a decoy receptor, neutralizing its ligand, IL‐33.…”
Section: Introductionmentioning
confidence: 99%
“…The circulating biomarker, soluble ST2 (sST2) has been shown to be a powerful independent prognosticator for patients with acute myocardial infarction (AMI)1, 2 as well as acute decompensated3, 4 and chronic5, 6, 7, 8, 9 HF. sST2, a member of the interleukin (IL)‐1 receptor‐like family of proteins, is released in response to myocyte stretch, and functions as a decoy receptor, neutralizing its ligand, IL‐33.…”
Section: Introductionmentioning
confidence: 99%
“…So far, only few studies have investigated GDF‐15 and sST2 in patients with non‐ischaemic DCM 21, 37. Although an association of both GDF‐15 and sST2 with sudden cardiac death was previously demonstrated, non‐ischaemic DCM represented one‐third to one‐half of these cohorts 24, 25, 37. Because of different aetiologies of the disease leading to different risks of AD,5, 8 it is of paramount importance to separately investigate ischaemic and non‐ischaemic heart failure patients.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation and myocardial fibrosis, with subsequent ventricular remodelling and impairment of systolic function, are important pathophysiological mechanisms for VTs in patients with DCM 19, 20. Both GDF‐15 and sST2 show strong correlations with myocardial stress and fibrosis,21, 22, 23 and have been associated with sudden cardiac death in DCM 24, 25…”
Section: Introductionmentioning
confidence: 99%
“…However, there are still only a few studies about sST2 in patients with stable CHF. Pascual-Figal et al 16 confirmed that sST2 levels (cut-off point, 0.15 ng/ml) are predictive of sudden cardiac death in patients with stable CHF and LV systolic dysfunction (LVEF ≤45%) at 1-year follow-up.The higher cut-off point obtained in our study (0.296 ng/ml) was presumably the result of poorer LV systolic function in the study population. Ky et al 17 conducted an analysis of 1141 outpatients with systolic CHF (LVEF = 32.2% ±17%) and showed that higher sST2 levels on enrollment were associated with a significantly increased risk of all-cause death or cardiac transplantation after a median follow-up of 2.8 years.…”
mentioning
confidence: 90%